2020
DOI: 10.1038/s41598-020-68263-0
|View full text |Cite
|
Sign up to set email alerts
|

Gait asymmetry, and bilateral coordination of gait during a six-minute walk test in persons with multiple sclerosis

Abstract: Gait impairments in persons with multiple sclerosis (pwMS) leading to decreased ambulation and reduced walking endurance remain poorly understood. our objective was to assess gait asymmetry (GA) and bilateral coordination of gait (BCG), among pwMS during the six-minute walk test (6MWT), and determine their association with disease severity. We recruited 92 pwMS (age: 46.6 ± 7.9; 83% females) with a range of clinical disability, who completed the 6MWT wearing gait analysis system. GA was assessed by comparing l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 56 publications
(91 reference statements)
3
24
0
Order By: Relevance
“…Also of note is that chronic gait asymmetry could also lead to increased risk of lower-limb overuse injuries and articular joint degeneration due to the increased weight bearing and propulsion demands placed on one lower limb during walking, in both pathological 69 – 72 and healthy populations 73 . Along these lines, gait asymmetry can be used as (i) a metric to assess pathology status, patients’ functional recovery or disease progression, (ii) a target for interventions aiming to improve gait performance, and (iii) outcome to evaluate and compare different gait rehabilitation programs interventions 43 , 55 , 74 77 . Interestingly, various rehabilitation programs have been shown to improve gait to a more symmetric gait pattern in individuals with lower-limb amputations (see for review 78 ), stroke survivors (see for review 79 ) or patients with Parkinson disease 80 , 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Also of note is that chronic gait asymmetry could also lead to increased risk of lower-limb overuse injuries and articular joint degeneration due to the increased weight bearing and propulsion demands placed on one lower limb during walking, in both pathological 69 – 72 and healthy populations 73 . Along these lines, gait asymmetry can be used as (i) a metric to assess pathology status, patients’ functional recovery or disease progression, (ii) a target for interventions aiming to improve gait performance, and (iii) outcome to evaluate and compare different gait rehabilitation programs interventions 43 , 55 , 74 77 . Interestingly, various rehabilitation programs have been shown to improve gait to a more symmetric gait pattern in individuals with lower-limb amputations (see for review 78 ), stroke survivors (see for review 79 ) or patients with Parkinson disease 80 , 81 .…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the prolonged tests are a better indicator of the ability of PwMS to perform the activities of daily living and have been evaluated for use in clinical practice and research [8,15,16]. Studies in PwMS [15,[17][18][19] and in other populations [20,21] have demonstrated that some walking variables measured during a 6MWT like walking velocity, cadence, or stride time could be altered across the 6MWT. These results suggest that the measurement of variables other than the classic distance to complete the 6MWT could provide a more detailed idea of the patients' performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to walking slower, fallers also walked with greater stance and swing time asymmetries. Recent investigations suggest that asymmetric gait is a robust measure characterizing the gait in PwMS and related to disease severity and falls 23 , 24 . Notably, asymmetric gait is not necessarily an uncoordinated gait 25 .…”
Section: Discussionmentioning
confidence: 99%